THE VALIDITY OF LEARNING MATERIAL ASSISTED AUGMENTED REALITY TECHNOLOGY IN THE TOPIC OF STRUCTURE AND FUNCTION OF PLANT TISSUE - Erti Hamimi; Sugiyanto Sugiyanto; Erni Yulianti; Vita Ria Mustikasari; Novida Pratiwi (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2021)
The Industrial Revolution 4.0 is a comprehensive transformation of all aspects of production in industry through the combination of digital and internet technology with conventional industries. The education sector is an important field that must adapt to the demands of the times so as not to be left behind. In the world of education, especially in subjects such as Basic Biology, there are many objects that are difficult to visualize in real terms, one of which is the topic of the Structure and Function of Plant Networks. The problem can be visualized using Augmented Reality (AR) technology. The purpose of developing AR-based teaching materials is to combine biology material by applying AR technology so that learning is more interesting, meaningful, and interactive, and students can observe objects in biological studies. The product specifications developed were in the form of Basic Biology I teaching materials consisting of the BIOAR application and augmented reality-based supplement books on the topic of Plant Tissue Structure and Function. This method of developing teaching materials used R & D (Research and Development) which consisted of (1) Research and Information collection, (2) Planning, (3) Development of teaching materials based on augmented reality, (4) Validation of teaching materials by experts. The validation results showed that this augmented reality-based teaching material was declared very valid with a value of 4.52.